Inspections – Key Role in Quality of Medicines - Shah, Manan; Shah, Vishal (Asian Journal of Pharmaceutical Research and Development, 2023)
Global patients depend on medications for their specific purposes. These drugs are manufactured both domestically and internationally. Regardless of where they are manufactured, the Food and Drug Administration (FDA) plays a pivotal role in the United States, regulating drugs, biologics, and devices by not only scrutinizing each marketing holder’s application but also guaranteeing that the product’s manufacturer complies with current good manufacturing practices (cGMP). This ensures that the product’s quality is consistent and is manufactured securely for its intended use.